A theoretical model of the diffusion process to spherical and isotropic fruits - Maldonado, Mariela (2014)
Many models are using now in order to can study of the table green olives diffusion process. Different models had been consistent in order to determinate the magnitude order of the diffusion coefficient effectiveness; we can to mention the thin plate model, the hollow cylinder and the hollow sphere model. But none them describe geometrically in a correct way this fruit. For this reason, we had developed a new model to spherical and isotropic fruits in order to can to adapt its diffusion behavior with the same geometry. So, all spherical isotropic fruit with pit are in conditions of to be treaty with this method